Increasing on-treatment hepatocellular carcinoma risk with decreasing baseline viral load in HBeAg-positive chronic hepatitis B - Won-Mook Choi; Gi-Ae Kim; Jonggi Choi; Seungbong Han; Young-Suk Lim (The Journal of Clinical Investigation, 2022)
BACKGROUND It is unclear whether the level of serum hepatitis B virus (HBV) DNA at baseline affects the on-treatment risk of hepatocellular carcinoma (HCC) in hepatitis B e antigen–positive (HBeAg-positive), noncirrhotic patients with chronic hepatitis B (CHB).METHODS We conducted a multicenter cohort study including 2073 entecavir- or tenofovir-treated, HBeAg-positive, noncirrhotic adult CHB patients with baseline HBV DNA levels of 5.00 log10 IU/mL or higher at 3 centers in South Korea between January 2007 and December 2016. We evaluated the on-treatment incidence rate of HCC according to baseline HBV DNA levels.RESULTS During a median 5.7 years of continuous antiviral treatment, 47 patients developed HCC (0.39 per 100 person-years). By Kaplan-Meier analysis, the risk of HCC was lowest in patients with baseline HBV DNA levels of 8.00 log10 IU/mL or higher, increased incrementally with decreasing viral load, and was highest in those with HBV DNA levels of 5.00–5.99 log10 IU/mL (P < 0.001). By multivariable analysis, the baseline HBV DNA level was an independent factor that was inversely associated with HCC risk. Compared with HBV DNA levels of 8.00 log10 IU/mL or higher, the adjusted HRs for HCC risk with HBV DNA levels of 7.00–7.99 log10 IU/mL, 6.00–6.99 log10 IU/mL, or 5.00–5.99 log10 IU/mL were 2.48 (P = 0.03), 3.69 (P = 0.002), and 6.10 (P < 0.001), respectively.CONCLUSION On-treatment HCC risk increased incrementally with decreasing baseline HBV DNA levels in the range of 5.00 log10 IU/mL or higher in HBeAg-positive, noncirrhotic adult patients with CHB. Early initiation of antiviral treatment when the viral load is high (≥8.00 log10 IU/mL) may maintain the lowest risk of HCC for those patients.FUNDING Patient-Centered Clinical Research Coordinating Center (PACEN) (grant no. HC20C0062) of the National Evidence-based Healthcare Collaborating Agency; National R&D Program for Cancer Control through the National Cancer Center (grant no. HA21C0110), Ministry of Health and Welfare, South Korea.